Pengaruh Deepfake terhadap Kepercayaan Publik pada Informasi Visual di Media Sosial - Muhammad Dhafin Atha Azka; Nadya Fitri Aulia; Farel Ananda; Purwanto Putra (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
This study aims to analyze the impact of deepfake content on the level of public trust in visual information on social media. Using a between-subjects experimental design, the study involved 20 active social media user respondents in Indonesia (aged 18-45 years) who were randomly divided into two groups: an experimental group (exposed to deepfake content) and a control group (exposed to original content). Data were collected through a questionnaire measuring three dimensions of trust: (1) perceived authenticity of the content, (2) source credibility, and (3) emotional impact. The t-test results showed significant differences (p < 0.05) between the two groups, with the deepfake group having lower trust scores on all dimensions (mean score: 2.4 vs. 4.2 for content authenticity; 2.8 vs. 4.4 for source credibility; 2.7 vs. 4.0 for emotional impact). Regression analysis revealed that education level (β = 0.35) and frequency of social media use (β = -0.27) significantly affected the level of trust. Pearson correlation findings also showed a strong positive relationship between perceived authenticity of content and trust levels (r = 0.72, p < 0.001). This study concludes that exposure to deepfake content significantly reduces public trust in visual information, with the effect compounded by intensive social media use and moderated by education level. The implication is that evidence-based media literacy strategies are needed to raise public awareness about deepfake technology, as well as stricter regulation of synthetic content on digital platforms.